Pelatihan dan Pendampingan Penyusunan Penelitian Tindakan Kelas bagi Guru SDIT Bilingual Alma Asy Syauqi Kota Cirebon - Dadan Setiawan; Dwi Anita Alfiani; Syibli Maufur; Ade Hidayat; Idah Faridah Laily; Ardian Ardian (Jurnal Pengabdian Pada Masyarakat, 2022)
TRAINING AND ASSISTANCE IN THE PREPARATION OF CLASSROOM ACTION RESEARCH FOR ALMA ASY SYAUQI BILINGUAL ISLAMIC ELEMENTARY SCHOOL TEACHERS, CIREBON CITY. Training and Assistance in the Preparation of Classroom Action Research for Bilingual IT Elementary School Teachers Alma Asy Syauqi, Cirebon City. The purpose of this activity is to provide teachers with an understanding of classroom action research and to train teachers to develop classroom action research. The number of participants in this activity was six teachers. This activity was carried out for approximately three weeks from November 5 to November 22, 2021 at the IT Bilingual Elementary School Alma Asy Syauqi, Cirebon City. The implementation of this activity has several steps including providing material on the basic concepts of classroom action research, models of classroom action research, the importance of classroom action research, and systematics of classroom action research. The next step is for the trainees to practice using the Mendeley application for technical citation and bibliography writing. Then practice compiling a class action research proposal. The methods used in this training activity are expository methods, lectures, questions and answers, discussions, and assignments to make a class action research proposal. The result of this activity is that the teachers have a good understanding of CAR and are able to prepare a class action research proposal well. The enthusiasm of the teachers in the implementation of the training activities was very good and this activity received a positive response from the head of the foundation, principals, and teachers who participated in the training.